KAJIAN PERENCANAAN PASAR INDUK KABUPATEN BADUNG DENGAN PENDEKATAN TATA RUANG, ARSITEKTUR, DAN BUDAYA LOKAL BALI - I MADE SASTRA WIBAWA; TJOKORDA ISTRI PRAGANINGRUM; ANAK AGUNG GDE SUTRISNA WIJAYA PUTRA; MADE WAHYU WIJAYA; I PUTU YANA HERMAWAN; I KETUT AGUS KARMADI (GANEC SWARA, 2024)
In the central market planning project in Badung Regency, Bali, the main objective was to develop an economic center that combines cultural elements with sustainable economic growth. The planning goes beyond the traditional paradigm of development by integrating cultural, social, environmental, architectural, civil engineering and economic factors, creating an entity that carries more value than just commercial transactions. The central market is intended to represent a balance between cultural heritage and the dynamics of modernity, with reference to the principles of Tri Hita Karana (balance with God, fellow humans, and the natural environment) as well as the concept of Hulu - Teben which directs the organization of space based on the flow of the river. The Tri Mandala and Sanga Mandala concepts guide the zone mapping and building orientation, optimizing air circulation and natural lighting. The market architecture adopts traditional Balinese elements such as limasan and jineng roof forms, and utilizes natural materials such as red bricks and temple stones. A purposeful and iconic signage system, including the Ratu Niang Sakti statue, became an important part of the design. The result is a synergy between cultural values and global progress, forming a neighborhood that functions not only as a place of transaction, but also as a vehicle for cultural preservation and a driver of inclusive economic growth. The project encourages active community participation in the development process, accelerates the welfare of local communities, and improves the competitiveness of the region. Thus, the project achieves its goal not only as physical infrastructure, but also as a platform that integrates cultural significance and economic dynamism within the framework of sustainable development